The welfare optimal distribution of Olympic Success considered as a public good - Loek F. M. Groot (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2007)
This study considers the performance of countries at the Olympic Games as a public good and investigates different welfare optimal distributions of Olympic success. First, it is argued that at the national level Olympic success, measured as the number of gold medals won, meets the two key conditions of a public good, nonrivalry and non-excludability. Second, it is demonstrated that standard income inequality measures as the Lorenz curve and Atkinson's measure can successfully be applied to the distribution of Olympic success. Four different distributions are considered: the actual distribution, the distribution according to population shares, the distribution under constant and declining marginal utility of medals and the one also taking production costs and declining marginal utility of per capita income into account. For the latter two, the rules for the welfare optimal distributions are stated, viz. equality of the marginal contributions to welfare and the Samuelson condition. At the end, a device is proposed to make the distribution of Olympic success more equitable.
Keywords: 330; Olympic Games; Public Goods; Externalities; Social Welfare